2010
DOI: 10.1111/j.1745-6584.2010.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Influence of Geology on E. coli and Arsenic in Aquifers of Bangladesh

Abstract: Arsenic in groundwater has been a concern in South and Southeast Asia for more than a decade. We explore here the possibility that hydrogeologic factors recently shown to influence the distribution of arsenic might also affect the level of contamination of shallow (<20 m) wells with microbial pathogens. A total of 96 shallow tube wells in two nearby villages of Bangladesh were surveyed during the wet and dry seasons, along with 55 deeper wells in neighboring villages. One of the two villages is located in a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 46 publications
3
63
2
Order By: Relevance
“…This prediction, based on recent data for the fecal indicator E. coli obtained in the context of As-related studies in Bangladesh [24], [25] is here borne out at the population level by the analysis of actual diarrheal disease patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prediction, based on recent data for the fecal indicator E. coli obtained in the context of As-related studies in Bangladesh [24], [25] is here borne out at the population level by the analysis of actual diarrheal disease patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Less attention has been paid, however, to the possibility that some categories of wells that are low in As could be particularly vulnerable to microbial contamination. The present analysis of a unique set of diarrheal disease data from Bangladesh is motivated by hydrogeological considerations suggesting that shallow tubewells that are low in As might be particularly prone to microbial contamination [24]. Monthly monitoring of 125 shallow tubewells in two separate regions of Bangladesh has since confirmed that groundwater pumped from shallow low-As wells is more likely to contain the fecal indicator E. coli than groundwater from shallow wells that are high in As [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the greater physical separation between deep wells and major surface sources of microbial contamination, such as latrines and ponds, may have provided a protective effect. 6,11 The incidence of childhood diarrhoea declined dramatically between 2005 and 2006, irrespective of water source (Fig. 2), but discussion of the reasons for this decline lie beyond the scope of this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 It has recently been shown, however, that groundwater pumped from shallow low-arsenic wells is more likely to be contaminated with human waste than groundwater from shallow high-arsenic wells because of the nature of local hydrogeology combined with the high population density and poor sanitation. 11,12 This raised the concern that the response of households to the testing of wells for arsenic could have increased exposure to microbial pathogens. More generally, faecal contamination of shallow groundwater may be one reason for the persistence of diarrhoeal disease in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between these indicators and fecal contamination or As concentrations in groundwater was unclear. Monitoring of a substantial number of shallow wells in Bangladesh has documented an inverse relationship between the fecal indicator E. coli and As concentrations (Leber et al, 2011; van Geen et al, 2011). This could be seen as an indication that human waste, if anything, inhibits the release of As to groundwater (McArthur et al, 2012).…”
Section: Introductionmentioning
confidence: 99%